Synthesis of NiO Nanostructures Using Cladosporium cladosporioides Fungi for Energy Storage Applications - Funda Ersoy Atalay; Dilek Asma; Harun Kaya; Alper Bingol; Pinar Yaya (Nanomaterials and Nanotechnology)
In this work, we produced nickel oxide nanostructures that show high electrochemical capacitive behaviour, using fungus - one of the most common life forms in nature. Cladosporium cladosporioides fungi are particularly attractive biotemplates due to their tubular structures. The nano‐ structured porous microtubes were prepared by chemical precipitation onto fungi. The morphological properties of the biosynthesized NiO microtubes were studied by transmission electron microscope (TEM). The Brunauer– Emmett–Teller (BET) surface area was found to be 119.72 m2 g-1 with an average pore size distribution of 7.5 nm. A maximum capacitance value of 334 F g-1 was observed at 0.8 A g-1, and a capacitance retention of approximately 95% was obtained after 1000 cycles.